Comparison Study on The Competence of Employee and Non-Employee Students in STIE Indonesia Pontianak - Jumardi Budiman (STKIP Singkawang, 2018)
The aim of this research was to know the different level of employee students and non-employee students competence in STIE Indonesia Pontianak. The research variables were viewed from 3 (three) aspects, they are cognitive, affective and psychomotor aspects. The method used in this research was quantitative comparative (Comparison study) with questionnaires as the tool of data collecting which were distributed to the 420 students as the research sample. The conclusion of this research was there were differences in cognitive and psychomotor aspects of employee and non-employee students and there was no difference in effective aspect.